2021
DOI: 10.3390/antiox10030480
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Plant Extracts and Phytoconstituents on Antioxidant Enzymes Activity and Gene Expression in the Prevention and Treatment of Impaired Glucose Homeostasis and Diabetes Complications

Abstract: Diabetes is a complex metabolic disorder resulting either from insulin resistance or an impaired insulin secretion. Prolonged elevated blood glucose concentration, the key clinical sign of diabetes, initiates an enhancement of reactive oxygen species derived from glucose autoxidation and glycosylation of proteins. Consequently, chronic oxidative stress overwhelms cellular endogenous antioxidant defenses and leads to the acute and long-standing structural and functional changes of macromolecules resulting in im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 103 publications
(138 reference statements)
1
25
0
Order By: Relevance
“…In several studies, the beneficial effects of medicinal herbs have been confirmed on the components of MetS such as dyslipidemia (Mihailović et al, 2021; Mollazadeh, Mahdian, & Hosseinzadeh, 2019; Nyakudya, Tshabalala, Dangarembizi, Erlwanger, & Ndhlala, 2020). Medicinal herbs may affect on blood lipid profile by their antioxidant properties and reducing inflammatory cytokines such as TNF‐α and IL‐1β (Mahdian et al, 2020).…”
Section: Effects Of α‐La On Lipid Profilementioning
confidence: 97%
See 1 more Smart Citation
“…In several studies, the beneficial effects of medicinal herbs have been confirmed on the components of MetS such as dyslipidemia (Mihailović et al, 2021; Mollazadeh, Mahdian, & Hosseinzadeh, 2019; Nyakudya, Tshabalala, Dangarembizi, Erlwanger, & Ndhlala, 2020). Medicinal herbs may affect on blood lipid profile by their antioxidant properties and reducing inflammatory cytokines such as TNF‐α and IL‐1β (Mahdian et al, 2020).…”
Section: Effects Of α‐La On Lipid Profilementioning
confidence: 97%
“…In several studies, the beneficial effects of medicinal herbs have been confirmed on the components of MetS such as dyslipidemia (Mihailovi c et al, 2021;Mollazadeh, Mahdian, & Hosseinzadeh, 2019;Nyakudya, Tshabalala, Dangarembizi, Erlwanger, & Ndhlala, 2020).…”
Section: Effects Of α-La On Lipid Profilementioning
confidence: 97%
“…The result presented above showed a decrease in C-reactive protein and interleukin-6 level in Gongronema latifolium and insulin treated group when compared with diabetic (DM only) group. The decrease in the C-reactive protein levels in the two treated group is an indication of the anti-inflammatory potential of G. latifolium which may be due to the flavonoid and polyphenols in the plant extract [29]. A study reported that flavonoids present in G. latifolium leaves extract are kaempherol, kaempferol 3-O-rutinoside, rutin and laricitrin-3-Oglucoside [30].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, strawberries can decrease pro-oxidant processes, causing oxidative stress in healthy subjects by increasing plasma antioxidants and reducing the production of reactive oxygen species through reposing phagocytes in peripheral blood [ 93 ]. Strawberry polyphenols may elevate the gene transcription of nuclear factor-erythroid 2 related factor 2 (Nrf2) that regulates the biosynthesis of different antioxidant enzymes [ 94 ]. Furthermore, they can have an impact on activity and expression of PPARs involved in several cellular processes such as lipid metabolism and fatty acid oxidation [ 95 ].…”
Section: Effect Of Phytochemicals and Medicinal Plants On Paraoxonase...mentioning
confidence: 99%